2006
DOI: 10.1080/03009740600904284
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor (TNF)α −308 G/G promoter polymorphism and TNFα levels correlate with a better response to adalimumab in patients with rheumatoid arthritis

Abstract: A relationship between DAS28 improvement, the -308 G/G polymorphism, and increased circulating TNFalpha levels was found in Chilean RA patients treated with adalimumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 17 publications
1
43
3
Order By: Relevance
“…We contacted the authors of these two studies, who reconfirmed their data. Nevertheless, analysis of the four remaining studies (8,13,15,16) showed no significant heterogeneity (I 2 ¼ 0%), and the overall difference in DAS28 score decreased, but remained significantly different from zero (difference ¼ 0.53, 95% CI: 0.18, 0.88, P ¼ 0.0033). Five of the six studies, which reported DAS28 score also used this as the criterion to determine responsiveness to the TNF-a inhibitor.…”
Section: Tnf-a à308 G/a Variant and Anti-tnf-a Agents D D O'rielly Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…We contacted the authors of these two studies, who reconfirmed their data. Nevertheless, analysis of the four remaining studies (8,13,15,16) showed no significant heterogeneity (I 2 ¼ 0%), and the overall difference in DAS28 score decreased, but remained significantly different from zero (difference ¼ 0.53, 95% CI: 0.18, 0.88, P ¼ 0.0033). Five of the six studies, which reported DAS28 score also used this as the criterion to determine responsiveness to the TNF-a inhibitor.…”
Section: Tnf-a à308 G/a Variant and Anti-tnf-a Agents D D O'rielly Et Almentioning
confidence: 99%
“…7 At present, there are a handful of small studies that have set out to examine whether the G to A polymorphism at position À308 in the promoter of the TNFa gene influences clinical response to TNF blockade in patients with moderate-to-severe RA. [8][9][10][11][12][13][14][15][16] Owing to the relatively small number of patients exposed to anti-TNF-a agents in all of the pharmacogenetic studies in RA to date, each individual study had insufficient power to conclusively determine if the À308 variant of the TNF-a gene would be helpful in predicting patients that respond poorly to TNF-a blockade. Lee et al 17 carried out a metaanalysis investigating the association of TNF-a À308 G/A polymorphism with responsiveness to TNF-a-blockers in RA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Marotte et al [16] reported controversial results that TNF-α -308 SNP was not associated with response to infliximab therapy in RA patients. In another report, TNFα -308 GG promoter polymorphism had better response to adalimumab therapy than GA phenotype in 81 active RA patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, one study has shown that patients bearing the GGC haplotype of TNF gene (-238G/-308G/-857C) in a homozygous form showed low response rate to ADA treatment (26), whereas in another study, TNF -308 homozygous (G/G) patients showed better response than heterozygous (G/A) patients (27). In other studies the development of antibodies directed against adalimumab has been shown to be associated with interleukin-(IL)10 polymorphisms (28).…”
Section: Discussionmentioning
confidence: 99%